Terrorism, environmental pollution, foreign direct investment (FDI), energy consumption, and economic growth: Evidences from China, India, Israel, and Turkey - Bildirici, Melike E. (SAGE PUBLICATIONS LTD, 2021)
In this paper, it was aimed to investigate the relation between economic growth, terrorism, foreign direct investment (FDI) inflow, environmental pollution, and energy consumption in China, India, Israel, and Turkey for a time span of 43 years from 1975 to 2017. Three different panel cointegration methods to determine the cointegration relation and two different causality methods to find the direction of causality were simultaneously used, since the presence of cointegration and direction of causality are fundamental to design economic policy and strategy. After similar results from panel cointegration tests were obtained, the causality tests were applied. Panel causality tests determined the evidence of uni-directional causality from terrorism, FDI, and energy usage to CO2 emission.
Keywords: Terrorism; environmental pollution; panel cointegration test; panel causality test; NORTH-SOUTH TRADE; PANEL-DATA; CO2 EMISSIONS; TESTS; COUNTRIES; COINTEGRATION; REGULATIONS; STATIONARITY; REGRESSION; CAUSALITY; Environmental Sciences & Ecology